Drying of almonds I: single particle - Chilka, A. G.; Ranade, V. V. (Indian Chemical Engineer, 2017)
Drying is an essential unit operation required in food processing industries, particularly in the dry fruits industry. Drying of almonds exhibit many characteristic features such as non-spherical shape, swelling/ shrinkage as a function of moisture content, uneven drying because of their peculiar shape and proximity to other almond kernels and so on. In this study, we have investigated the drying of almonds through experiments and computational modelling. In this regard, Mettler Toledo Halogen moisture analyzer unit was used to conduct experiments for a single almond kernel. In this widely used equipment, internal air flow patterns and therefore heat and mass transfer depend on natural circulation of air. A detailed three-dimensional computational fluid dynamics (CFD) model was used to simulate the air flow pattern, heat and mass transfer in the drying unit. Carefully designed experiments with a single almond kernel were carried out at different temperatures to estimate key parameters of interest (drying kinetics and effective diffusivity). The CFD model was also used to quantify non-uniform heat and mass transfer and therefore non-uniform drying of a single almond kernel. The presented approach, models and results might be useful to improve the performance of drying units in industrial systems. The results and models presented here will also provide a basis for further work on multiple almond kernels and on tray dryer unit. © 2017 Indian Institute of Chemical Engineers